Greek-Bulgarian Dispute Through the Prism of Russian Diplomacy: From the Exarchy to the Schism (1870‒1872) - Laković, Maja R. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The compromise policy of the Russian government served Ignatiyev as a cover for his obvious favour to the Bulgarian side, with the goal of achieving not only church but also political independence of Bulgaria. During the Greek-Bulgarian religious conflict, the Russian ambassador had a high degree of freedom in his independent actions. The motives of all participants in the dispute corresponded more to a political than to an ecclesiastical struggle. He also considered the Proclamation of the Bulgarian Exarchy a personal triumph, which he interpreted as a victory for the Slavs in Turkey, while it was actually a victory for the Bulgarian side. The proclamation of the Bulgarian Exarchate, and not long after, the schism, permanently changed the relations between Russia and the Patriarchate of Constantinople.